Gospel Allegiance What Faith in Jesus Misses for Salvation in Christ - Bates, Matthew W. 1977- (Grand Rapids Brazos Press, 2019)
Challenging popular misconceptions about the biblical gospel, Matthew Bates shows that it is different, wider, and more beautiful than we have been led to believe.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books